The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/j.1681-4835.2014.tb00469.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Communication Technologies on the Performance of SMEs in a Developing Economy: Nigeria as a Case Study

Abstract: Informed by Social Shaping Theory (modified), this paper presents a research that examines the impact of communication technologies (mobile telephony, personal computer and internet facilities) on the performance of small and medium businesses in Lagos state, Nigeria. Results indicate that SMEs operating in different socio‐economic settings present varying performance results from the use of communication technology tools. The study was undertaken through a firm survey and also a number of semi‐structured inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 23 publications
0
6
1
Order By: Relevance
“…In fact, the Internet is more important rather than the number of computers in the firm. Our results are not in line with findings ofRufai (2014), suggesting that the adoption of computer signalled an improvement in business performance of studied firms in terms of operational cost reduction, sale/customer increase, business expansion, increase profitability, improve service quality/delivery, fraud reduction and general operational and administrative efficiency. Similar to our resultsNotta & Vlachvei (2013), indicate the low web-site adoption rate for the surveyed SMEs, as well as that the websites are mainly informative about the general characteristics of the firm such as location and contact.…”
contrasting
confidence: 99%
“…In fact, the Internet is more important rather than the number of computers in the firm. Our results are not in line with findings ofRufai (2014), suggesting that the adoption of computer signalled an improvement in business performance of studied firms in terms of operational cost reduction, sale/customer increase, business expansion, increase profitability, improve service quality/delivery, fraud reduction and general operational and administrative efficiency. Similar to our resultsNotta & Vlachvei (2013), indicate the low web-site adoption rate for the surveyed SMEs, as well as that the websites are mainly informative about the general characteristics of the firm such as location and contact.…”
contrasting
confidence: 99%
“…SMEs now invest significant amounts of financial resources in technology to strengthen their competitive positions (Ghobakhloo et al, 2012). Rufai (2014) also found that usage technology by SMEs positively impacts business performance in terms of cost reduction, enhanced productivity as well as improved revenue and profitability.…”
Section: Discussionmentioning
confidence: 99%
“…Technology is an important factor for SMEs' product mobility within and across national boundaries. Studies such as Oluwatayo (2014) and Rufai (2014) have found that use of technology by SMEs positively impacts business performance in terms of cost reduction, enhanced productivity as well as improved revenue and profitability.…”
Section: Introductionmentioning
confidence: 99%
“…The quantitative and qualitative paradigm elements were also adopted in the study. This was adopted because of allowing a mixed research method strategy (Rufai, 2014). The mixed research method strategy was adopted for the purpose of: enabling the possibility for findings collaboration through triangulation; allowing the potential weaknesses of methods associated with each strategy to be offset to each other; allowing in-depth, comprehensive and broad investigation as well as better understanding of the phenomenon through research completeness (Rufai, 2014).…”
Section: 2mentioning
confidence: 99%
“…This was adopted because of allowing a mixed research method strategy (Rufai, 2014). The mixed research method strategy was adopted for the purpose of: enabling the possibility for findings collaboration through triangulation; allowing the potential weaknesses of methods associated with each strategy to be offset to each other; allowing in-depth, comprehensive and broad investigation as well as better understanding of the phenomenon through research completeness (Rufai, 2014). Moreover, the aim was also to enhance the research credibility and the likelihood of results/findings integrity as well as eliciting respondent's diversity from the sample (Bryman, 2008).…”
Section: 2mentioning
confidence: 99%